EFFECT OF CHICKEN FEATHER WASTE ON CONCRETE MIXING ON COMPRESSIVE STRENGTH AND FLEXURAL STRENGTH - Sutarno, Sutarno; Rahmawati, Diah; Masvika, Hendra (ASTONJADRO, 2021)
The materials that are often used in the world of construction both in bridges, water structures, and buildings is concrete. The characteristic of concrete is that it is strong withstand compressive forces, but weak in resisting tensile forces. Therefore, it is necessary to improve the characteristics of the concrete. Improving the characteristics of the concrete can be done by applying a fiber mixture to the concrete. There are two types of fibers used as a concrete mixture, namely synthetic fibers and natural fibers. The research conducted was concrete using chicken feather waste fiber which was categorized as natural fiber with a fiber length of 3 cm, the grade of the concrete used was 20 MPa and the percentage of additional chicken feather waste was 0%, 1%, and 2% of the volume of concrete. The test is the compressive strength and flexural strength of the concrete using a specimen cylinder 15x30 cm and beam 15x15x60 cm. Each percentage of chicken feather waste that is used as a concrete mixture is 5 samples. From the test results, it was found that the concrete with the addition of 0% chicken feathers obtained an average compressive strength value of 200.78 kg/cm2, concrete with the addition of 1% chicken feather fiber, the compressive strength value increased to 215.09 kg/cm2 and concrete with the addition of chicken feather fiber 2 % has a compressive strength value of 197.54 kg/cm2. Meanwhile, the flexural strength values obtained were 24.00 kg/cm2, 23.03 kg/cm2, 21.08 kg/cm2 for the percentage of 0%, 1% and 2% fibers, respectively. This shows that the concrete with the addition of bristle fibers the chicken has decreased the compressive strength value when it has reached its optimum level. While the addition of the percentage of chicken feathers to the flexural strength value does not have much effect on the flexural strength of the concrete which tends to decrease. This is influenced by the characteristics of the chicken feathers which are difficult to bond with the concrete as well as being easy to absorb water, so that the concrete takes a longer time to dry after the maintenance of the concrete.